SQ3R IMPLEMENTATION IN TEACHING READING COMPREHENSION(A Case Study of Eighth Grade Students at One State MTs in Sumedang - Masruuroh, Mila Siti (2015)
This research aimed to describe the implementation of SQ3R in teaching reading comprehension and to identify students' responses toward the implementation of SQ3R. Moreover, it examined the benefits of SQ3R in teaching reading comprehension in Indonesia. This research used a qualitative case study conducted at one State MTs in Sumedang. It involved one class of the eighth grade which consists of 30 students. The data were collected through observation, interview, and document analysis. The data from the three instruments were analyzed qualitatively. The results of this research showed that the implementation of SQ3R helped the students to comprehend English texts. The students also responded the implementation of SQ3R positively. They focused while reading English texts by using SQ3R. They were also interested and enthusiastic in doing the tasks. In addition, SQ3R helped them to write questions from the texts, to rewrite the information by their own words, to write a report or a summary about the texts, and to enrich their vocabularies. In conclusion, SQ3R helped the students in reading English texts. Therefore, SQ3R is recommended to be implemented in teaching reading comprehension. Keywords : SQ3R, Reading, Reading Comprehension Penelitian ini bertujuan untuk mendeskripsikan implementasi SQ3R dalam pengajaran pemahaman membaca dan untuk mengidentifikasi tanggapan siswa terhadap implementasi SQ3R. Selain itu, penelitian ini juga menguji manfaat dari SQ3R dalam pengajaran membaca di Indonesia. Penelitian ini menggunakan studi kasus kualitatif yang dilaksanakan di salah satu MTs Negeri di Sumedang. Penelitian ini melibatkan satu kelas VIII yang terdiri dari 30 siswa. Data-data dalam penelitian ini dikumpulkan melalui observasi, wawancara, dan analisis dokumen. Data dari ketiga instrumen tersebut dianalisis secara kualitatif. Hasil penelitian ini menunjukan bahwa implementasi SQ3R membantu siswa memahami teks-teks Bahasa Inggris. Para siswa juga memberikan tanggapan positif terhadap implementasi SQ3R ini. Mereka fokus ketika membaca teks Bahasa Inggris dengan menggunakan SQ3R. Mereka juga tertarik dan antusias dalam mengerjakan tugas-tugas tersebut. Selain itu, SQ3R membantu mereka dalam menulis pertanyaan-pertanyaan dari teks, menulis kembali informasi dengan kata-kata sendiri, menulis laporan atau rangkuman mengenai teks, dan memperkaya kosa kata mereka. Dapat disimpulkan bahwa SQ3R membantu para siswa untuk membaca teks-teks Bahasa Inggris. Oleh karena itu, disarankan SQ3R dapat diimplementasikan dalam pengajaran membaca. Kata Kunci : SQ3R, Membaca, Pemahaman Membaca.